ChemInform Abstract: Type‐I Clathrates of K7.69(2)Cu2.94(6)Ge43.06(6) and Rb8Ag2.79(4)Ge43.21(4). Issue 37 (September 2015) - Zhang, Hui; Xu, Xuguang; Li, Wei; Mu, Gang; Huang, Fu‐Qiang; Xie, Xiao‐Ming
Abstract The title compounds are synthesized from mixtures of the elements in a molar ratio of K/Rb:Cu/Ag:Ge = 8:2.7:43.3 (Ta tubes, 700 °C, 7 d) and characterized by powder XRD, magnetization and heat capacity measurements, and DFT calculations.